You, Writing! A Guide to College Composition - Glynn, Alexandra; Hallsten-Erickson, Kelli; Swing, Amy Jo; Open Textbook Library (Open Textbook Library, 2018)
This text is meant to be used in any first year College Composition class or as a general guide to college writing. The book focuses on writing as a process, not a product. The goal is to help students discover their own writing process, tryin g out different methods and strategies to find what works best for them
Chapter One: Why Write? -- Chapter Two: A Writing Process for Every Writer -- Chapter Three: Defining Audience and Purpose -- Chapter Four: Exploring: Finding a Topic -- Chapter Five: Writing a Thesis -- Chapter Six: Organizing -- Chapter Seven: Drafting -- Chapter Eight: Revising -- Chapter Nine: Editing -- Chapter Ten: Proofreading -- Chapter Eleven: Research Process
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Rhetoric -- Textbooks